2007
DOI: 10.1016/j.ydbio.2007.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Target gene selectivity of the myogenic basic helix–loop–helix transcription factor myogenin in embryonic muscle

Abstract: The myogenic regulatory factors MyoD and myogenin are crucial for skeletal muscle development. Despite their importance, the mechanisms by which these factors selectively regulate different target genes are unclear. The purpose of the present investigation was to compare embryonic skeletal muscle from myogenin(+/+) and myogenin(-/-) mice to identify genes whose expression was dependent on the presence of myogenin but not MyoD and to determine whether myogenin-binding sites could be found within regulatory regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 41 publications
6
43
0
1
Order By: Relevance
“…Equally surprising is the partial repression of MyoD. While it is not unexpected that myogenin would contribute to the expression of MyoD, the expression of MyoD in Myog-null animals is not significantly altered (7,19,58). How CIITA represses Myog and MyoD is not currently understood, but we hypothesize that the recruitment of CIITA through the interaction with myogenin causes a repression at promoters that other transcriptional activators cannot overcome.…”
Section: Discussionmentioning
confidence: 83%
“…Equally surprising is the partial repression of MyoD. While it is not unexpected that myogenin would contribute to the expression of MyoD, the expression of MyoD in Myog-null animals is not significantly altered (7,19,58). How CIITA represses Myog and MyoD is not currently understood, but we hypothesize that the recruitment of CIITA through the interaction with myogenin causes a repression at promoters that other transcriptional activators cannot overcome.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, we have previously shown that the hormone induces myosin heavy chain (MHC) and myogenin in the early stage of differentiation of C2C12 cells grown in low-serum medium (Buitrago et al 2012). The presence of myogenin ensures MHC expression and modulates the subsequent myotube development, demonstrating that myogenin acts early in the determination of myoblast differentiation (Davie et al 2007). In this work, 1,25D induced an acute and steady increase in myogenin expression in C2C12 WT cells, while myogenin protein levels remained undetectable in C2C12-VDR cells and when p38 was inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Both P21 waf1/Cip1 and p27 Kip1 are CKIs; however, they have specific actions in myogenic differentiation (el-Deiry et al 1994, Guo et al 1994. The induction of p27 Kip1 CKI is an early critical step of the N-cadherin-dependent signaling involved in myogenesis, showing an active role of p27 Kip1 CKI in the decision of myoblasts to undergo differentiation (Messina et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Myogenin regulates various genes necessary for skeletal muscle differentiation, including the expression of myosin heavy chain, troponin and another muscle-specific transcription factor, MRF4 (Perry and Rudnick, 2000;Davie et al, 2007). Interestingly, while osteogenic markers started to appear at a Pi concentration of 3~5 mM, the inhibition of myogenesis manifested in a decrease of the fusion index, and myogenin expression was not observed until the Pi concentration reached 7 mM.…”
Section: Pi-induced Osteogenesis and Inhibited Myogenesis In Skeletalmentioning
confidence: 99%